2016
DOI: 10.1016/j.cell.2016.10.043
|View full text |Cite
|
Sign up to set email alerts
|

A Dietary Fiber-Deprived Gut Microbiota Degrades the Colonic Mucus Barrier and Enhances Pathogen Susceptibility

Abstract: SUMMARY Despite the accepted health benefits of consuming dietary fiber, little is known about the mechanisms by which fiber deprivation impacts the gut microbiota and alters disease risk. Using a gnotobiotic mouse model, in which animals were colonized with a synthetic human gut microbiota composed of fully sequenced commensal bacteria, we elucidated the functional interactions between dietary fiber, the gut microbiota and the colonic mucus barrier, which serves as a primary defense against enteric pathogens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

107
2,103
11
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,148 publications
(2,242 citation statements)
references
References 51 publications
107
2,103
11
21
Order By: Relevance
“…27,28 Exogenous perturbations may upset this balance further to induce acute disease pathogenesis. Such perturbations include withdrawal of dietary fiber (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 Exogenous perturbations may upset this balance further to induce acute disease pathogenesis. Such perturbations include withdrawal of dietary fiber (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to Streptococcus, Akkermansia, Bacteroides, and other bacterial genera that have an extensive repertoire of enzymes devoted to catabolizing host-associated glycoproteins in the gut and oral cavity (24,(37)(38)(39)(40), the primary CF pathogen, P. aeruginosa, is not known to encode any glycosidases used in the breakdown of respiratory mucins. Indeed, we demonstrate here that strain PA14 uses intact mucins inefficiently compared to its carbohydrate and amino acid monomeric constituents (glucose and Casamino Acids).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, all mucosal sites throughout the human body harbor both commensal and pathogenic organisms that possess mucin-degrading enzymes capable of deriving nutrients from host (22)(23)(24). Indeed, several studies have described the degradation and utilization of mucins by CF-associated microbiota (25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…A recent study, using a simplified model of the human gut microbiome in gnotobiotic mice, found that low dietary intake of fibre increased the susceptibility of colitis by reducing the mucus layer [63]. Mice colonised with the simplified model of the human gut microbiome were fed a fibrerich or fibre-free diet.…”
Section: Diet Low In Fibre Confers Susceptibility For Colitismentioning
confidence: 99%